Microcomputer programs for graphic analysis of nucleic acid and protein sequences. - Mount, D W (1984)
Four computer programs are described which allow two amino acid or DNA sequences to be compared for homology, the results being displayed in a 2-dimensional array on a printer page. The programs also may be used to visualize repeated sequences or dyad symmetry within a DNA sequence. Two of the four programs may be used with any printer, the other two require a printer with graphics capability. Many options are available including using only a portion of a sequence, specifying a window to demonstrate more significant structures and special restrictions on matching such as excluding the third base in a codon. Written in the C programming language, the programs run under the CP/M 80 operating system, and may be copied in binary format through a modem. They are also available for the IBM/PC.